EXPERIMENTAL DETERMINATION OF FROST HEAVE FORCES IN THE GROUND - Vyalov,S. S.; Yegorov,N. I. (1970)
Any rational system for constructing building foundations in regions where permafrost and deep seasonal freezing are prevalent is impossible without due regard for the heaving forces which are built up during freezing of the ground. However, the data on the actual magnitude of these forces are incomplete. One factor which hinders experiments for determining heaving forces under field conditions appears to be undeveloped methods and the lack of enough simple procedural methods for such determinations. The purpose of the work was to test a new system for determining heaving forces under field conditions and development of some recommendations for using such a system. (Author) Trans. from Akademiya Nauk SSSR. Institut Merzlotovedeniya. Trudy, v14 1958.